International Criminal Law Enforcement Against International Terrorist Networks: A Case Study of the Hambali Terrorism Network and Its Legal Implications - Rasyad, Pasha Athallah; Hadhani, Muhammad Gading Bintang; Tambunan, Daniel (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Terrorism is a transnational crime that has evolved into an increasingly complex and organized form of threat, operating through global financing networks, cross-border recruitment, digital communication technologies, and decentralized structures that transcend national jurisdictions. These characteristics render domestic legal frameworks insufficient to address the operational dynamics of modern terrorist networks. This study aims to analyze the enforcement of international criminal law against international terrorist networks and examine its legal implications for national jurisdictions. Using a normative juridical method supported by a statute approach and case approach, this research examines international legal frameworks—including thematic conventions and United Nations Security Council resolutions—as well as relevant national regulations, particularly Indonesia’s Law No. 5 of 2018 on the Eradication of Terrorism. The findings indicate that despite the existence of numerous instruments encouraging global cooperation, the enforcement of international criminal law continues to face significant challenges, such as the absence of a universally accepted definition of terrorism, inconsistencies between national legal systems, and limited mechanisms for cross-jurisdictional implementation. Furthermore, the study emphasizes the importance of upholding human rights principles—especially fair trial guarantees, non-refoulement, and protection against torture—within counter-terrorism efforts. This research concludes that effective eradication of international terrorist networks requires stronger harmonization between international and national legal frameworks, enhancement of inter-state cooperation mechanisms, and continuous development of law enforcement capacities to address the evolving nature of transnational terrorism.